2007
DOI: 10.1590/s0004-27492007000200025
|View full text |Cite
|
Sign up to set email alerts
|

Simetria das medidas morfométricas do segmento anterior entre olhos adelfos pela biomicroscopia ultra-sônica (UBM)

Abstract: This study demonstrated that symmetry of morphometric measurements between right and left eyes is expected to occur, provided these eyes have similar refractive errors and biometric measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
3
1
1
Order By: Relevance
“…In this study, no statistical significant differences were found between the ID1 of complete and incomplete PIC, or in relation to the ID1 of normal eyes (Tables 1, 2 and 3) (7)(8)(9) . In fact, the ID1 measurement was performed at 500 µm from the scleral spur, which in most eyes with PIC does not correspond to the position of the plateau iris.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…In this study, no statistical significant differences were found between the ID1 of complete and incomplete PIC, or in relation to the ID1 of normal eyes (Tables 1, 2 and 3) (7)(8)(9) . In fact, the ID1 measurement was performed at 500 µm from the scleral spur, which in most eyes with PIC does not correspond to the position of the plateau iris.…”
Section: Discussioncontrasting
confidence: 66%
“…In fact, the ID1 measurement was performed at 500 µm from the scleral spur, which in most eyes with PIC does not correspond to the position of the plateau iris. Moreover, table 1 shows that, with the exception of ID1, all the other parameters presented statistically significant lower values than those found in normal eyes (7)(8)(9) .…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…[29] в своих исследованиях выявили значительное уменьшение глубины и сужение угла передней камеры непосредственно после витр эктомии в 15 глазах с последующей газовоздушной тампонадой, в нескольких случаях имела место отслойка цилиарного тела. F. Marigo [30] при исследовании с помощью ультразвуковой биомикроскопии глубины передней камеры, ширины угла ПК на расстоянии 500 мкм от склеральной шпоры, дистанции трабекулоцилиарных отростков и толщины цилиарного тела не выявил достоверных изменений биометрических параметров указанных структур через 1 мес после операции витрэктомии.…”
Section: обзоры литературыunclassified